Circulating small dense LDL, endothelial injuring factors and fibronectin in healthy postmenopausal women - Muzzio, Maria Luz (2007)
BACKGROUND: In postmenopausal women (PMW), an adverse lipoprotein pattern and high risk of coronary artery disease has been described. Studies of the mechanisms promoting the higher atherogenic risk observed in healthy PMW are relevant. We evaluated the interactions among several circulating factors involved in the endothelial injury and inflammation in relation to LDL characteristics, beyond LDL cholesterol. METHODS: Lipoprotein profile, including apolipoproteins A-I and B, small dense LDL, hepatic lipase, cholesterol transfer protein (CETP), LDL composition and oxidability were assessed in PMW (n=30) in comparison to premenopausal (PreMW, n=28). The following emerging factors were measured: homocysteine, phospholipase A2, ferritin, hs-CRP and fibronectin from extracellular vascular matrix. Insulin-resistance was evaluated by waist circumference, HOMA and TG/HDL cholesterol ratios. RESULTS: The risk index apo B/apo A-I was significantly increased in PMW (p<0.0001), PMW showed higher proportion of small dense LDL which correlated with the increase in hepatic lipase activity (p<0.005) and with insulin-resistance markers (p<0.05), but not with CETP. Phospholipase A2 (p<0.05), homocysteine (p<0.005), hs-CRP (p<0.005), fibronectin (p<0.05) and ferritin (p<0.0001) were increased in PMW. LDL oxidability positively correlated with waist (p<0.02), homocysteine (p<0.05), fibronectin (p<0.05), hs-CRP (p<0.04), phospholipase A2 (p<0.05), and small dense LDL (p<0.01). After adjusting by menopausal condition, age and waist, LDL oxidability remained associated with waist (beta: 0.35, p=0.047), homocysteine (beta: 0,36 p<0,038), fibronectin (beta: 0,41 p=0.05), and small dense LDL (beta: 0.36, p=0.027). CONCLUSIONS: Evaluation of classic and non-traditional circulating risk factors in hypoestrogenism reflected endothelial and subendothelial inflammation and subclinical atherogenic processes.